The Most Common Students’ Epistemological Obstacles in Relations and Functions - Firda, Nadiatun; Suryadi, Didi; Nasir, Nurihan (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
Epistemological obstacles are obstacles that cannot be avoided by students. There are many epistemological obstacles experienced by students in understanding scientific knowledge. In this case, students experience cognitive constraints in understanding a learning topic, such as Relations and Functions. The topic of Relations and Functions is one of the important topics for learning further topics. However, there are still students who cannot understand this topic perfectly due to various epistemological obstacles they experience. Therefore, this study aims to describe the epistemological obstacles on the topic of relation and function. This study was qualitative research with 22 junior high school students who have studied the topic of relation and function. The results of this study are in the form of epistemological obstacles experienced by students, namely obstacles to understanding the concepts of relations and functions, obstacles to understanding the concepts of relations and functions in different contexts, obstacles to determining the domain, codomain, and range, and obstacles to presenting relations and functions to various representations. This research is expected to be used as a reference by teachers to minimize the occurrence of epistemological obstacles in the learning process. In addition, one of the efforts that can be made by teachers and researchers to minimize epistemological obstacle is by making Didactical Design Research (DDR) that supports the development of student knowledge epistemically. Hambatan epistemologis merupakan suatu hambatan yang tidak dapat dihindari oleh siswa. Terdapat banyak kendala epistemologis yang dialami oleh siswa dalam memahami pengetahuan ilmiah. Dalam hal ini, siswa mengalami kendala kognitif dalam memahami suatu materi pembelajaran, seperti Relasi dan Fungsi. Topic Relasi dan Fungsi merupakan salah satu topic penting untuk mempelajari topic-topic selanjutnya. Namun, masih terdapat siswa yang tidak dapat memahami topic ini dengan sempurna dikarenakan berbagai hambatan epistemologis yang dialaminya. Oleh karena itu, penelitian ini bertujuan untuk mendeskripsikan hambatan epistemologis pada topic relasi dan fungsi. Penelitian ini merupakan penelitian kualitatif dengan subjek berupa 22 siswa sekolah menengah pertama yang telah mempelajari topic relasi dan fungsi. Hasil penelitian ini berupa hambatan-hambatan epistemologis yang dialami oleh siswa yaitu hambatan memahami konsep relasi dan fungsi, hambatan memahami konsep relasi dan fungsi pada konteks yang berbeda, hambatan menentukan domain, kodomain, dan range, serta hambatan menyajikan relasi dan fungsi ke berbagai representasi. Penelitian ini diharapkan dapat digunakan sebagai acuan bagi guru untuk meminimalkan terjadinya hambatan epistemologis dalam proses pembelajaran. Selain itu, salah satu upaya yang dapat dilakukan oleh guru maupun peneliti untuk meminimalkan hambatan epistemologis yaitu dengan membuat Didactical Design Research (DDR) yang mendukung perkembangan pengetahuan siswa secara epistemic.